Drivers of Buy Now Pay Later (BNPL) Adoption in Emerging Markets: A Qualitative Exploration of Shopee PayLater Users in Bogor City, Indonesia - El Hasan, Sawqi Saad (Pascasarjana STIE Miftahul Huda, 2025)
This study investigates the factors driving the adoption of Shopee PayLater, a